International Human Rights Law in Japan: The View at Thirty - Webster, Timothy (Columbia Journal of Asian Law, 2010)
Japan has incorporated international human rights law in various ways over the past thirty years. By ratifying the International Covenant on Social, Economic and Cultural Rights (“ICESCR”) and International Covenant on Civil and Political Rights (“ICCPR”) in 1978,1 Japan signaled a new openness to international law, and rapidly internalized a range of global norms. In the early 1980s, the legislature (Diet) actively engaged in this process, revising existing laws and passing new ones to implement international legal obligations. In the 1990s, judges began to apply international treaties directly in areas like criminal procedure and minority rights. At the same time, the Diet withdrew from its role as in- terpreter, arbiter and codifier of international law, either unable or unwill- ing to pass new laws to fulfill Japan’s international legal obligations. In the new millennium, more conversant with international norms and protections, courts increasingly apply international law in human rights litigation. The Diet debates, but does not legislate, leaving the essential task of disseminating contemporary international human rights norms to judges. [1] See International Covenant on Civil and Political Rights, Dec. 16, 1966, 999 U.N.T.S. 171 (en- tered into force for Japan on Sept. 21, 1979) (hereinafter ICCPRI; International Covenant on Eco- nomic, Social and Cultural Rights, Dec. 16, 1966, 993 U.N.T.S. 3 (entered into force for Japan on Sept. 21, 1979) [hereinafter ICESCR]. For information on Japan’s ratification of international hu- man rights law, see U. Minn. Hum. Rts. Libr. Ratification of Human Rights Treaties-Japan, http://www l.umn.edu/humanrts/research/ratification-japan.html (last visited Mar. 2, 2010).